Fetal malformation anencephaly with placenta accreta spectrum (increta): Two different tales in a pregnancy - A rare case report - Indu Lata; Ruchi Gupta; Amrit Gupta; Pallavi Prasad (Wolters Kluwer Medknow Publications, 2022)
Placenta accreta spectrum (PAS) disorders (accreta, increta, and percreta) are rare but are potentially life-threatening obstetric conditions of high maternal and fetal or neonatal morbidity and mortality. In the patient at risk for accreta, obstetrical ultrasonography should be performed and it can be complemented with magnetic resonance imaging. In suspected cases, a multidisciplinary team with clinical expertise should be involved. Anencephaly is a major lethal fetal anomaly of severe central nervous system malformation and the most common type of neural tube defect (NTD). Although the etiology of anencephaly remains unclear, various maternal-related environmental and genetic risk factors have been reported. Termination of pregnancy is offered for all prenatally diagnosed cases. We are presenting management of the rare case of a pregnant woman having placenta increta with fetal NTD malformation in the form of anencephaly.